2019
DOI: 10.1038/s41598-019-55204-9
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal potential of secondary metabolites involved in the interaction between citrus pathogens

Abstract: Numerous postharvest diseases have been reported that cause substantial losses of citrus fruits worldwide. Penicillium digitatum is responsible for up to 90% of production losses, and represent a problem for worldwide economy. In order to control phytopathogens, chemical fungicides have been extensively used. Yet, the use of some artificial fungicides cause concerns about environmental risks and fungal resistance. Therefore, studies focusing on new approaches, such as the use of natural products, are getting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…We also observed that fungisporin analogues were grouped in this cluster. A fragmentation pattern with typical ions observed at [M + H] + m/z 120.08, m/z 219.15 and m/z 247.14 was previously described for compounds Phe-Val-Val-Phe and Phe-Val-Val-Tyr (19,29,30) (Fig. S5B and S5C).…”
Section: Tryptoquialanine a Is A Component Of P Digitatum Evssupporting
confidence: 61%
See 2 more Smart Citations
“…We also observed that fungisporin analogues were grouped in this cluster. A fragmentation pattern with typical ions observed at [M + H] + m/z 120.08, m/z 219.15 and m/z 247.14 was previously described for compounds Phe-Val-Val-Phe and Phe-Val-Val-Tyr (19,29,30) (Fig. S5B and S5C).…”
Section: Tryptoquialanine a Is A Component Of P Digitatum Evssupporting
confidence: 61%
“…These results suggested that tryptoquialanines are involved in the fruit protection against insects that could compete with the fungus for the rotten fruit (18). In co-culture models, it has been observed that P. digitatum tryptoquialanines were present in the confrontation zone with citrus pathogens, suggesting that tryptoquialanines participate in antifungal defense mechanisms that could provide competitive advantages during infection of the citrus host (19).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The most harmful phytopathogenic fungi of oranges are Penicillium digitatum, which causes the green mold disease, responsible for about 90% of post-harvest losses (Costa et al, 2019b;Papoutsis et al, 2019), and Penicillium italicum Wehmer, the causing agent of the blue mold disease. The latter disease develops more slowly, however, it presents higher resistance to cold (Whiteside et al, 1993;Palou et al, 2002;Iqbal et al, 2012Iqbal et al, , 2017 and to low water availability (Plaza et al, 2003), easily spreading and contaminating a greater number of healthy oranges.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, the pulp properties of impacted fruit are the main research focus, such as the sugar-acid ratio and flavor, and the peels have not been well investigated [6]. Previous studies have shown that metabolites are involved in many biological functions in the development of fruits, such as pigment, antifungal, and antioxidant properties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%